Crossings - Steel, Danielle (London : Warner Books, 1999)
A novel featuring two married couples whose lives become intertwined during World War II. Armand, who at the start of the story is the French Ambassador to the United States, is married to an American, Lianne. Steel magnate, Nick stays with his selfish wife, Hillary, to avoid losing his son.
Keywords: World War, 1939-1945 -- Fiction; Love stories